Study Of Students\' Perception Of Mobile Learning In Probability Lessons - Atan @ Mohd Salleh, Mislina (2010)
This study aimed at examining students\' perception and experiences of mobile learning in Probability lessons. It is guided by \"ASSURE\" instructional design model as an instructional framework and involved three phases.